PENGARUH PENGGUNAAN METODE PEMBELAJARAN THE LEARNING CELL TERHADAP MOTIVASI BELAJAR PKN SISWA KELAS VIII SMP NEGERI 1 SINABOI SATU ATAP KABUPATEN ROKAN HILIR - Suraini Suraini '; Gimin Gimin '; Zahirman Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the low students‟ motivation to learn civics at SMPN 1 Sinaboi District One Rokan Hilir. Formulation of the problem in this research was: How was the effectiveness of using the learning cell toward students„ motivation of PKn of VIII grade of SMPN 1 Sinaboi District One Atap Rokan Hilir? This study aims to determine the effectiveness of using the learning cell method toward students‟ motivation in learning civics of VIII grade students of SMP Negeri 1 Sinaboi One Atap Rokan Hilir. This research was conducted in SMP Negeri 1 Sinaboi District One on August until September 2015. This research was descriptive quantitative with population in this research was VIII grade students of SMP Negeri 1 Sinaboi District One Atap. The sample in this study were drawn based on the technique of